Malaria during pregnancy and transplacental transfer of Kaposi sarcoma-associated herpesvirus (KSHV) antibodies: a cohort study of Kenyan mother and child pairs - Sabourin, Katherine R. (Infect Agent Cancer, 2020)
BACKGROUND: Kaposi sarcoma-associated herpesvirus (KSHV) seroprevalence in sub-Saharan African children can range up to 50% by age 2 years but factors affecting early age of KSHV infection are not well understood. Malaria during pregnancy has been associated with hindered transplacental transfer of antibodies to several pathogens but whether it affects transplacental transfer of KSHV antibodies is unknown. We aimed to determine if in utero malaria exposure reduced the transfer of KSHV antibodies across the placenta. METHODS: A cohort study in Kisumu, Kenya enrolled pregnant women at their first antenatal clinic (ANC) visit and followed them through delivery. We included 70 KSHV-positive, HIV-negative mothers and their children. KSHV antibody levels were measured by ELISA (K8.1, ORF73) and multiplex assay (K8.1, ORF73, K10.5, ORF38, ORF50). Transplacental transfer of antibodies was measured by the cord to maternal blood ratio (CMR) of KSHV antibodies. Malaria during pregnancy was defined as detection of Plasmodium falciparum (Pf) DNA at any ANC visit or delivery. Among women with malaria during pregnancy, we examined time of last malaria infection prior to delivery (< 27 vs. 27+ weeks gestation) and malaria incidence rate (MIR) (episodes/100 person-weeks). RESULTS: KSHV seroprevalence (positive for K8.1 or ORF73 by ELISA) among pregnant women was 88%. Neither malaria during pregnancy, malaria infection timing, nor MIR were associated with maternal delivery KSHV antibody blood levels. Maternal delivery and cord blood KSHV antibody levels were highly correlated but these correlations did not differ by malaria during pregnancy. KSHV transplacental antibody transfer was not associated with malaria during pregnancy, malaria infection timing, nor MIR. CONCLUSIONS: Malaria during pregnancy does not appear to affect transfer of KSHV antibodies across the placenta. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13027-020-00336-1.